Vaccine Hesitancy and Readiness Among University Students: A Cross-Sectional Study - Karthikeyan A; Kamalakumar Uthayanan; Prashanth M; Venkateswaramurthy Nallasamy; Sudha Muthusamy (The Bioscan, 2025)
Background: Vaccine hesitancy is a recognized barrier to optimal COVID-19 vaccination coverage, particularly among youth populations. This study examines COVID-19 vaccine acceptance, hesitancy, and associated factors among university students in Southern India, with emphasis on public health policy implications. Methods: A cross-sectional survey was conducted between June and August 2022 among unvaccinated students at a pharmacy college in Tamil Nadu, India. A structured online questionnaire captured socio-demographic data, attitudes towards COVID-19 vaccination, perceived barriers, and information sources. Chi-square tests and multivariate analyses were applied using IBM SPSS v22, with p<0.05 considered statistically significant. Results: Of 401 respondents, 346 (87.1%) were unvaccinated; 248 (71.7%) expressed willingness to vaccinate, while 98 (28.3%) were hesitant. Key predictors of hesitancy included inadequate perceived safety information (p=0.047), perception that vaccination is profit-driven (p=0.034), and concerns regarding long-term safety studies (p=0.055). Social media was the dominant information source for hesitant individuals (87.8%). Despite hesitancy, most participants acknowledged vaccination as essential for pandemic control Conclusion: While in the study, the acceptance rates were high, persistent misconceptions and mistrust highlight the need for targeted information campaigns. Public health policy must address misinformation, strengthen safety communication, and leverage trusted channels to reach student populations. KEYWORDS: COVID-19 Vaccines; Vaccination Refusal; Health Knowledge, Health Policy; Vaccination Misinformation